(untitled) (Chemical Engineering Research Bulletin, 2023)
Water is very essential to avoid illness and enhance the quality of life. So, it’s necessary to have access to highquality water. Khulna city in Bangladesh is facing a scarcity of clean water; high saline water is also a problem in this region. So, the study aims at identifying contaminated water by collecting samples from different areas of Khulna. Water quality testing is carried out as part of the study to ensure that the community receives clean water and they can be aware of the quality of such water. Samples taken from different areas were tested in the laboratory. The analysis involved measuring several quality parameters including pH, turbidity, hardness, dissolved oxygen (DO), and biochemical oxygen demand (BOD). The pH levels were observed to be within the acceptable range, with the Sonadanga area showing slightly alkaline water at a pH of 8.1. However, the turbidity levels in the Bhairab River were extremely high at 307 NTU, far exceeding the Bangladeshi standard of 10 NTU, the DO levels across samples were reported between 9.6 to 10.8 mg/L, which are generally acceptable for drinking water. The BOD levels were also found to comply with safety standards, indicating that the water could potentially be suitable for drinking if proper treatment methods are applied. Overall, while some water sources show adequate quality, the prevalence of contamination and the looming water crisis highlight an urgent need for improved water management and treatment strategies in Khulna City. Chemical Engineering Research Bulletin 23 (2023): 97-102